PENGGUNAAN METODE SOSIODRAMA DALAM PENINGKATAN PEMBELAJARAN BAHASA INDONESIA BAGI SISWA KELAS V SD. - Wati, Undi Eka (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: Application of Sociodrama Method in Increase of Indonesia Language Learning for Fifth Grade Student Elementary School. The purposes of the research are: describe application of sociodrama method, to increase learning, and identify problems and solutions in the application of sociodrama method to increase Indonesia language learning especially speak skill and literature appreciation (drama) for fifth grade student elementary school. Subject of this research are students in fifth grade consist of 16 students elementary school. This study is a Collaborative Classroom Action Research that was held in three cycle. Each cycle consist of planning, implementation, observation, and reflection. The results show that the application of steps sociodrama method to increase Indonesia language learning especially speak skill and literature appreciation (drama) for fifth grade student elementary school. Keywords: sociodrama method, Indonesia language learning Abstrak: Penggunaan Metode Sosiodrama dalam Peningkatan Pembelajaran Bahasa Indonesia bagi Siswa Kelas V SD. Tujuan penelitian ini adalah: mendeskripsikan penggunaan metode sosiodrama, meningkatkan pembelajaran dan menemukan kendala serta solusi dalam peningkatan pembelajaran Bahasa Indonesia khususnya keterampilan berbicara dan apresiasi sastra (drama) di kelas V SD. Subjek penelitian ini adalah siswa kelas V SD berjumlah 16 siswa. Penelitian ini merupakan Penelitian Tindakan Kelas Kolaboratif yang dilaksanakan dalam tiga siklus. Tiap siklus mencakup tahap perencanaan, pelaksanaan, observasi dan refleksi. Hasilnya menunjukkan bahwa penggunaan metode sosiodrama dapat meningkatan pembelajaran Bahasa Indonesia khususnya keterampilan berbicara dan apresiasi sastra (drama) di kelas V SD.   Kata Kunci: metode sosiodrama, pembelajaran bahasa Indonesia